2007
DOI: 10.1029/2007jc004112
|View full text |Cite
|
Sign up to set email alerts
|

Role of aquifer heterogeneity in fresh groundwater discharge and seawater recycling: An example from the Carmel coast, Israel

Abstract: [1] A case study is shown in which the pattern of submarine groundwater discharge and of seawater recycling is controlled by local hydrogeological variability. The coastal aquifer in Dor Bay is composed of two units: a partly confined calcaranitic sandstone (Kurkar) and an overlying loose sand. Groundwater in the Kurkar has elevated activities of 222 Rn ($390 dpm/L) and relatively low 224 Ra/ 223 Ra activity ratios (3-4), while the sand groundwater is significantly less radiogenic (6-90 dpm/L) and shows higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…These values are indeed evident in southern Jordan, away from the Dead Sea, where 222 Rn activities in the sandstone Disi aquifer groundwater are only ∼400-700 dpm/L (Vengosh et al, 2009), which is similar to the activities found in sandstone aquifers elsewhere (e.g. Krishnaswami et al, 1982;Tricca et al, 2001;Weinstein et al, 2007). Given the 10% limit of 222 Rn contribution from the rock into the groundwater, also the radon activities of thousands of dpm/L observed in the TZG and KS groundwater (Appendix A, Fig.…”
Section: Excess 222 Rn Anomalymentioning
confidence: 74%
See 2 more Smart Citations
“…These values are indeed evident in southern Jordan, away from the Dead Sea, where 222 Rn activities in the sandstone Disi aquifer groundwater are only ∼400-700 dpm/L (Vengosh et al, 2009), which is similar to the activities found in sandstone aquifers elsewhere (e.g. Krishnaswami et al, 1982;Tricca et al, 2001;Weinstein et al, 2007). Given the 10% limit of 222 Rn contribution from the rock into the groundwater, also the radon activities of thousands of dpm/L observed in the TZG and KS groundwater (Appendix A, Fig.…”
Section: Excess 222 Rn Anomalymentioning
confidence: 74%
“…Similarly, 222 Rn activities in the thermal springs of the eastern catchment (EC, Salameh, 1996, Appendix A) vary between ∼6000 and 60,000 dpm/L, while the activity that could be produced by the rocks is no more than 6000 dpm/L (assuming U concentration of 0.5-1 ppm in the sandstone rock and porosity of 0.2). Moreover, the above activities are a maximum estimate, since usually no more than 10% of the radon is effectively ejected to the pore space fluid (Kigoshi, 1971;Krishnaswami et al, 1982;Tricca et al, 2001;Weinstein et al, 2007), which reduces the expected 222 Rn activities to less than 600-1200 dpm/L in both aquifers. These values are indeed evident in southern Jordan, away from the Dead Sea, where 222 Rn activities in the sandstone Disi aquifer groundwater are only ∼400-700 dpm/L (Vengosh et al, 2009), which is similar to the activities found in sandstone aquifers elsewhere (e.g.…”
Section: Excess 222 Rn Anomalymentioning
confidence: 98%
See 1 more Smart Citation
“…Submarine groundwater discharge (SGD) is a global phenomenon observed in numerous shallow water sites (Burnett et al, 2001;Li et al, 1999;Moore, 1996;Swarzenski et al, 2006;Taniguchi & Iwakawa, 2004;Weinstein et al, 2007). SGD is a path for groundwater outflow that may have a substantial effect on water budget of coastal aquifers (e.g., Moore, 2010), as well as coastal water quality (e.g., Johannes, 1980;Moore, 2010) and seafloor morphology (e.g., Orange et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Optimal management of coastal aquifers is becoming increasingly important due to population growth and climate change, which potentially affects water quality, ecosystem health and diversity, and water-supply reliability [1][2][3][4][5]. Surface water and groundwater are intrinsically linked systems [6][7][8][9]. Areas around streams, rivers, lakes and coastal environments represent zones of interaction and transition between the two systems, where dissolved constituents such as pollutants can be diluted, exchanged, transformed, or degraded.…”
Section: Introductionmentioning
confidence: 99%